Comparative evaluation of media used for detection of Salmonella spp - G. S. Skitovich; K. V. Serova; N. B. Shadrova; O. V. Pruntova (Ветеринария сегодня)
The paper demonstrates evaluation results for productive and selective capacities of domestic and imported chromogenic nutrient media (Bismuth sulphite agar and xylose lysine deoxycholate agar (XLD agar)). The productivity ratio of imported and domestic XLD agar amounted to over 0.58 and selectivity ratio - to less than 2 Ig. The productivity ratio of imported Bismuth sulfate agar was higher than the productivity of the domestic one and amounted to over 0.19. The selective properties of the both media are similar and amount to 5 Ig. Based on the evidence found, imported Bismuth sulfate agar and domestic or imported XLD agar can be recommended for use in the experiments for detection of Salmonella spp in food products.